CPU COOLING OF DESKTOP COMPUTER BY PARALLEL MINIATURE HEAT PIPES - Feroz, Chowdhury Md.; Uddin, Ahmed Imtiaz (Journal of Mechanical Engineering, 2010)
Heat transfer performance of parallel miniature heat pipes (MHPs) of 2.8 mm ID used for cooling desktop computer with different working fluids is presented in this paper. In cooling desktop processors, MHPs consists of six single tube heat pipes connected by a copper block at the evaporator section and fifteen parallel copper sheets used as external fins at the condenser section. Acetone and ethanol are used as working fluid. The copper block is placed above the heat source (on the top of the processor) and the condenser section is provided with external fins perpendicular to the MHPs. Heat transfer characteristics of MHPs using different working fluids are determined experimentally, based on the principle of phase. The experimental results show that, the maximum and steady state temperature of the processor has been reduced significantly by using MHPs with acetone as working fluid instead of conventional cooling fan. Additional use of a fan at the condenser section results much lower processor surface temperature for both working fluids. Key words: CPU cooling; Desktop processor; Heat transfer performance; Miniature Heat Pipe; Working fluid. DOI: 10.3329/jme.v40i2.5351 Journal of Mechanical Engineering, Vol. ME 40, No. 2, December 2009 104-109